Refining the adriamycin‐induced focal segmental glomerulosclerosis mouse model to improve reproducibility and animal welfare - Haochen Jiang; Salma Althobaiti; Braeden Pinkerton; Xin Fu; Zhenshan Jia; Kirk W. Foster; Geoffrey M. Thiele; Troy J. Plumb; Dong Wang (Animal Models and Experimental Medicine)
Abstract Background Reliable animal models are crucial to drug development for focal segmental glomerulosclerosis (FSGS), a rare kidney disease. Variability in success rates in literature and significant ethical concerns with animal welfare necessitate further optimization of adriamycin (ADR)–induced FSGS model developed on BALB/c mice. Methods High‐performance liquid chromatography (HPLC) was used to assess ADR stability in water and upon light exposure. To identify the optimal ADR level, single intravenous ADR injections with dosing levels from 10 to 17 mg/kg body weight were administered to BALB/c mice to induce FSGS‐like pathology. Body weight and proteinuria of FSGS mice were monitored and analyzed for FSGS model–associated morbidity. Animals were euthanized for hematological and kidney histological assessments 8 weeks post induction. To identify the suitable experiment time frame of the ADR‐induced FSGS mouse model, a longitudinal study was performed, with an 11‐week continuous monitoring of the symptoms. Results ADR was found to be unstable in aqueous media and light sensitive. A dosing level of 10.5 mg/kg of ADR was optimal for consistent FSGS mouse model induction on BALB/c strain, characterized by minimal mortality and sustained FSGS‐like symptoms. Findings from the longitudinal study suggest that 6 weeks post ADR induction may represent the peak of FSGS pathology severity in this mouse model. This time frame may be used for FSGS drug development projects. Conclusion Based on the outcome from this study, we identified the optimal ADR dosing level and model testing duration. A standard operating procedure (SOP) for the ADR‐induced FSGS mouse model was established to facilitate FSGS basic research and drug development.